2020
DOI: 10.1101/2020.06.18.157933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Acute Respiratory Distress and Cytokine Storm in Aged, SARS-CoV-2 Infected African Green Monkeys, but not in Rhesus Macaques”

Abstract: 26SARS-CoV-2 induces a wide range of disease severity ranging from asymptomatic 27 infection, to a life-threating illness, particularly in the elderly and persons with comorbid 28 conditions. Up to now, SARS-CoV-2 has infected more than five million and led to more 29 than 300,000 deaths worldwide. Among those persons with serious COVID-19 disease, 30 acute respiratory distress syndrome (ARDS) is a common and often fatal presentation. 31 SARS-CoV-2-induced ARDS is difficult to treat clinically, and new ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…S2). Consistent with our results, infection studies show that rhesus monkeys (Macaca mulatta), longtailed macaques (M. fascicularis) and vervets (Chlorocebus sabaeus) are permissive to infection by SARS-CoV-2, and go on to develop COVID-19 like symptoms [11][12][13][14]16 . Our results based on protein modeling offer potentially better news for monkeys in the Americas (platyrrhines).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…S2). Consistent with our results, infection studies show that rhesus monkeys (Macaca mulatta), longtailed macaques (M. fascicularis) and vervets (Chlorocebus sabaeus) are permissive to infection by SARS-CoV-2, and go on to develop COVID-19 like symptoms [11][12][13][14]16 . Our results based on protein modeling offer potentially better news for monkeys in the Americas (platyrrhines).…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, the overall pattern of our results is being borne out by infection studies on a few species that are used as biomedical models. So far, all catarrhine species tested by infection studies, including rhesus macaques, longtailed macaques, and vervet monkeys 13,14,64 have exhibited COVID-19-like symptoms in response to infection, including large lung and other organ lesions 13 and cytokine storms 14 . In contrast, marmosets did not exhibit major symptoms in response to infection 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported the development of the AGM as a promising animal model of human COVID-19 [10]. Other studies have subsequently reported similar findings [11,12]. The focus of the current study was to assess a more natural route of human exposure, specifically an exposure mimicking an infection resulting from mucosal exposure to infectious droplets expelled from close quarter exposure to a sneeze, cough, or even speech in order to begin characterization of lung pathology in the early convalescence phase of COVID-19.…”
Section: Discussionsupporting
confidence: 54%
“…Both small animal models and nonhuman primates (NHP) may prove valuable in triaging the most promising medical countermeasures prior to use in humans. Hamsters and ferrets are currently being used as immunocompetent small animal models of COVID-19 [3][4][5] while several NHP models have been quickly developed [6][7][8][9][10][11][12]. Among the nonhuman primate models evaluated the African green monkey (AGM) appears to best recapitulate the most salient features of human COVID-19 [10][11][12].…”
Section: Introductionmentioning
confidence: 99%